Taxonomic note: the fossil clawed lobster, Metanephrops elongatus Hu & Tao, 2000 (Nephropidae), is a nomen dubium but definitely not a Metanephrops - Tshudy, Dale; Chan, Tin-Yam (Zootaxa, 2014)
Metanephrops is an extant, clawed lobster genus (Family Nephropidae) with a very distinctive, carinate and spiny cephalothorax. It is the most speciose extant genus of clawed lobster, with 18 Recent species known. It is a deepwater genus with very large eyes; most species are known from deeper than 150 meters. Some species, nonetheless, are of commercial importance and marketed as “scampi”.